Sustainable Building Safety within Dhaka's Supply Chain Network: Analysing the Global Response to Disasters in Ready-Made Garment Factories - Munir, Shagufta Trishna (Curtin University, 2022)
The research investigated the prospects of sustaining the building safety regulatory reforms introduced in the RMG industry of Bangladesh mainly Dhaka, between 2013-2019 through transfer of social technology via transnational agencies. It further examined allocation of responsibility among each actor for building safety failures in the past. It obtained insight into duty of care among primary actors involved in safety planning, regulating and operating the RMG factories for promoting sustainable safety of Dhaka’s built environment.